Multiparty coordination under time pressure: The social organization of handball team time-out activities - Meyer, C.; von Wedelstaedt, U. (Embodied activities in face-to-face and mediated settings, 2019)
In the course of a handball game, coaches can address their team only at 60-second time-outs. Time pressure, the involvement of other staff, thousands of cheering spectators, and other environmental conditions lead to condensed interaction. Analyzing recordings taken during fieldwork (First German Leagues and national teams), we identify common `time-out practices` used across genders, teams, and coaches. These include semiotic resources and embodied practices by which participation frameworks and joint attention are attained, actions are performed, made recognizable, and ordered. We show how these practices are effective not despite but because of the `adverse` conditions. Our study has implications for interaction research more generally: we demonstrate how talk must be viewed as embodied activity itself, requiring bodily effort and skill by multiple persons involved.